Self-reported functional, communicative, and critical health literacy on foodborne diseases in Accra, Ghana - Gupta, S.; Tutu, R.A.; Boateng, J.; Busingye, J.D.; Elavarthi, S. (Tropical Medicine and Health, 2018)
Background Although substantial progress has been made in reducing total mortality resulting from foodborne diseases, diarrheal illness are still the second most common illnesses among children. In Ghana, foodborne diseases have consistently been among the top 20 causes of outpatient illness over the last couple of decades. This study, therefore, examines health literacy on foodborne diseases and the relative effects of health literacy on self-rated health. Methods Foodborne diseases are major causes of morbidity and mortality globally. A mixed-method approach was used for this study. A survey questionnaire and an in-depth interview guideline were administered to samples of 401 and 30 individuals, respectively. We undertook reliability and validity analyses. ANOVA and chi-square tests were undertaken to assess bivariate association between health literacy and demographic variables as well as health status. Ordinal logistic regression models were used to examine the relative effects of health literacy on self-rated health status controlling for individual characteristics. Results The instrument was internally consistent (Cronbach alpha = 0.744) and valid. On health literacy, 40% of the respondents reported not to require help when they are given information on foodborne diseases to read by a doctor, nurse, or pharmacist. Approximately 60% of respondents need help with completing or filling out hospital documents. Educational level was found to be positively related to functional health literacy. Ordinal logit regression models showed that health literacy is a predictor of self-rated health after controlling for demographic variables. Conclusion Functional literacy is relatively low in the community. There is a positive association between educational level and functional health literacy. The study has also demonstrated the direct positive relationship between health literacy and health status controlling for covariates. Subsequent studies will need to examine multiple level dimensions of health literacy with direct link between specific foodborne diseases and health literacy.
Keywords: Health literacy; Foodborne diseases; Urban slums; Tropical medicine; Ghana